Navigating Stress in the School Environment: Challenges, Coping Strategies and Students’ Well-being - Ningrum, Wa Ode Nirmala; Kusumawardhani, Anita; Yulindrasari, Hani; Budiman, Nandang; Sardin (GoAcademica Research & Publishing, 2025)
Stress can seriously affect the mental health and academic performance of students, especially when they have to face various pressures at school. Effective stress management and strong social support from their environment may help students reduce the negative effects of stress and improve their well-being. This study aims to explore the sources and impacts of stress, the coping strategies of high school students and their implications for education. The research employs a qualitative approach that emphasises the collection of descriptive and narrative data and efforts to understand the context and meaning behind the collected data. In terms of data collection, the researchers gathered important information using various techniques, such as participatory observation, in-depth interviews, and document analysis. The subjects of this study consisted of four students: two students from Madrasah Tsanawiyah (MTs) Grade VIII (one female and one male) and two students from Madrasah Aliyah (MA) Grade X (one female and one male), located in Bandung City, Indonesia. The study found that stress was a common experience among students, influenced by personal, school, and family contexts, making it essential to design appropriate support strategies. Interview results indicated that while students coped with stress in different ways, there was an urgent need to create a sensitive educational environment and improve access to professional support to help them achieve well-being. Therefore, it is crucial for schools to provide resources and create a positive learning environment to support students' mental health and academic performance.